Mechanistic study of TFE3 breakage in TFE3-rearranged renal cell carcinoma: the perspective of non-canonical DNA structures and their stability - Zhang, Xiaopo; Dang, Qinshuang; Pan, Xinghe; Deng, Zhenggen; Xu, Yanhao; Gan, Weidong; Guo, Hongqian (Frontiers in Genetics, 2025)
Background/ObjectivesTo address the unelucidated mechanisms of breakpoint formation in TFE3-rearranged renal cell carcinoma (TFE3-rRCC), this study characterizes breakpoint distribution within the TFE3 gene. We further explore how non-canonical DNA structures and their thermodynamic stability fluctuation may act as predisposing factors for the genomic instability driving these characteristic translocations.MethodsTFE3 breakpoints were identified in a cohort of 31 TFE3-rRCC tumor samples. The chi-square test was used to assess the statistical significance of breakpoint clustering. To investigate potential structural determinants, we predicted the distribution of G-quadruplex-forming sequences and palindromic motifs. Moving beyond simple motif density, we calculated the local Gibbs free energy changes (ΔG) associated with DNA secondary structures using Mfold and RNAfold to model thermodynamic stability across the TFE3 gene. This thermodynamic stability fluctuation was quantified as the maximum absolute local change in folding free energy (|dΔG|). Finally, this correlation between thermodynamic stability fluctuation and breakpoint location was validated by analyzing the 13 most frequently rearranged genes reported in the COSMIC database.ResultsA significant breakpoint cluster was identified within intron 5 of TFE3, containing 23 of 31 breakpoints (74.19%; chi-square test, P < 0.05). While the simple density of G-quadruplex or palindromic motifs did not directly correlate with breakpoint locations, a strong association with local thermodynamic stability fluctuation was observed. The region within intron 5 exhibited the highest thermodynamic stability fluctuation. This result suggests that regions of high thermodynamic stability fluctuation are correlated with increased susceptibility to DNA breakage. This finding was corroborated in the COSMIC dataset, where breakpoints in 12 of the 13 most frequently rearranged genes were similarly located near peaks of high |dΔG|.ConclusionOur findings indicate that breakpoint events in TFE3-rRCC are non-randomly clustered within intron 5. This clustering correlates strongly with regions characterized by high thermodynamic stability fluctuation (|dΔG|) of potential non-canonical DNA secondary structures. The principle that elevated local thermodynamic stability fluctuation is a feature of breakpoint locations was supported by analysis of a broader set of oncogenes, suggesting that high local thermodynamic stability fluctuation is a common feature of translocation-prone regions in cancer, representing a plausible, though not proven, contributor to genomic fragility.